2022
DOI: 10.3389/fnmol.2022.852368
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylated Human Tau Accumulates at the Synapse, Localizing on Synaptic Mitochondrial Outer Membranes and Disrupting Respiration in a Mouse Model of Tauopathy

Abstract: Neurogenerative disorders, such as Alzheimer’s disease (AD), represent a growing public health challenge in aging societies. Tauopathies, a subset of neurodegenerative disorders that includes AD, are characterized by accumulation of fibrillar and hyperphosphorylated forms of microtubule-associated protein tau with coincident mitochondrial abnormalities and neuronal dysfunction. Although, in vitro, tau impairs axonal transport altering mitochondrial distribution, clear in vivo mechanisms associating tau and mit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 148 publications
0
12
0
Order By: Relevance
“…Mitochondria dysfunction is a prominent early feature in the pathogenesis of AD, which has been linked to tau phosphorylation and aggregation in AD patients and multiple animal models [ 52 ]. Interestingly, Trease et al examined synaptic and non-synaptic brain mitochondria of 5- and 8-month-old htau mice, which express wild-type human tau in all 6 isoforms in the absence of murine tau [ 53 ]. Using subcellular proteomics, bioenergetics assessment, and metabolic pathway analysis, the authors revealed alterations in multiple pathways with oxidative phosphorylation yielding the strongest negative activation score for synaptic mitochondria of 8-month-old mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria dysfunction is a prominent early feature in the pathogenesis of AD, which has been linked to tau phosphorylation and aggregation in AD patients and multiple animal models [ 52 ]. Interestingly, Trease et al examined synaptic and non-synaptic brain mitochondria of 5- and 8-month-old htau mice, which express wild-type human tau in all 6 isoforms in the absence of murine tau [ 53 ]. Using subcellular proteomics, bioenergetics assessment, and metabolic pathway analysis, the authors revealed alterations in multiple pathways with oxidative phosphorylation yielding the strongest negative activation score for synaptic mitochondria of 8-month-old mice.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic forms of tau were found to associate preferentially with synaptic mitochondria, and the maximal respiration of htau synaptosomes was impaired. Thus, apparently, the accumulation of non-mutant human tau at the synapse may compromise proper mitochondrial operation with detrimental consequences for synaptic functioning [ 53 ]. We also observed a decreased expression of genes implicated in extracellular matrix and immune functions in our 5xFADxhtau-KI model at an older age.…”
Section: Discussionmentioning
confidence: 99%
“…Some omics studies have provided explanations for the concept that Aβ accumulation is a major cause of mitochondrial dysfunction and consequently triggers the AD phenotype [67,72,73]. As research progressed, the effect of tau on mitochondrial function has been gradually confirmed [74] as well as the production and growth of Aβ aggregation and tau hyperphosphorylation [77]. This is a terrible "vicious circle" that will eventually lead to an irreversible deterioration of AD.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Accumulation of pathogenic tau is highly associated with neuronal damage and cognitive defects observed in AD (Xia et al, 2021;Trease et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, specific soluble and oligomeric species of tau that are abnormally phosphorylated at AD associated sites have been identified as pathogenic forms (Zheng et al, 2020; Xia et al, 2021). Accumulation of pathogenic tau is highly associated with neuronal damage and cognitive defects observed in AD (Xia et al, 2021; Trease et al, 2022).…”
Section: Introductionmentioning
confidence: 99%